Aortic Valve Dysfunction and Aortic Dilation in Adults with Coarctation of the Aorta. (14th June 2013) - Clair, Mathieu; Fernandes, Susan M.; Khairy, Paul; Graham, Dionne A.; Krieger, Eric V.; Opotowsky, Alexander R.; Singh, Michael N.; Colan, Steven D.; Meijboom, Erik J.; Landzberg, Michael J.
Abstract Objectives To determine the prevalence of aortic valve dysfunction, aortic dilation, and aortic valve and ascending aortic intervention in adults with coarctation of the aorta (CoA). Background Aortic valve dysfunction and aortic dilation are rare among children and adolescents with CoA. With longer follow‐up, adults may be more likely to have progressive disease. Methods We retrospectively reviewed all adults with CoA, repaired or unrepaired, seen at our center between 2004 and 2010. Results Two hundred sixteen adults (56.0% male) with CoA were identified. Median age at last evaluation was 28.3 (range 18.0 to 75.3) years. Bicuspid aortic valve (BAV) was present in 65.7%. At last follow‐up, 3.2% had moderate or severe aortic stenosis, and 3.7% had moderate or severe aortic regurgitation. Dilation of the aortic root or ascending aorta was present in 28.0% and 41.6% of patients, respectively. Moderate or severe aortic root or ascending aortic dilation (z‐score > 4) was present in 8.2% and 13.7%, respectively. Patients with BAV were more likely to have moderate or severe ascending aortic dilation compared with those without BAV (19.5% vs. 0%; P < 0.001). Age was associated with ascending aortic dilation (P = 0.04). At most recent follow‐up, 5.6% had undergone aortic valve intervention, and 3.2% had aortic root or ascending aortic replacement. Conclusion In adults with CoA, significant aortic valve dysfunction and interventions during early adulthood were uncommon. However, aortic dilation was prevalent, especially of the ascending aorta, in patients with BAV.